2020
DOI: 10.1111/1346-8138.15422
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor necrosis factor‐α DNA are elevated in psoriasis

Abstract: In psoriasis, tumor necrosis factor (TNF)‐α is a key pro‐inflammatory cytokine that activates keratinocytes to produce other inflammatory mediators. In addition, increased serum or plasma TNF‐α levels are considered to be biomarkers of psoriasis. Circulating cell‐free DNA (cfDNA) originates from apoptotic or necrotic cells and reflects the severity of cellular damage. Although cfDNA has recently attracted attention as a marker in the diagnosis and prognosis of various disorders, there are few reports of its cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…It has been reported that TGF-β can activate Smad2 and Smad3 (38). Moreover, multiple studies have found that Smad4 loss on its own does not initiate tumor formation, but can promote fibrosis initiated by other genes, such as KRAS activation in pancreatic duct adenocarcinoma and APC inactivation in renal diseases (39). In this study, we found that LINC01234 knockdown downregulated the expression of p-Smad2, p-Smad3 in liver cancer cells.…”
Section: Discussionmentioning
confidence: 47%
“…It has been reported that TGF-β can activate Smad2 and Smad3 (38). Moreover, multiple studies have found that Smad4 loss on its own does not initiate tumor formation, but can promote fibrosis initiated by other genes, such as KRAS activation in pancreatic duct adenocarcinoma and APC inactivation in renal diseases (39). In this study, we found that LINC01234 knockdown downregulated the expression of p-Smad2, p-Smad3 in liver cancer cells.…”
Section: Discussionmentioning
confidence: 47%
“…Similar to the other diseases described above, the presence of cfDNA, both in serum and plasma, can reflect the cellular damage in this disease coming from apoptotic or necrotic cells [92,93]. Recently, Sakamoto et al investigated whether the TNF-α gene was present in cfDNA and whether its levels could be used as a biomarker in psoriasis [94]. TNF-α is a key proinflammatory cytokine that activates keratocytes, exacerbating an inflammatory process and constituting an inseparable element of psoriasis [95].…”
Section: Circulating Free Dna In Other Autoimmune Disordersmentioning
confidence: 92%
“…Isolation of cfDNA and amplification via ddPCR were performed as described previously. 5 Clinical profiles of all patients are shown in Table 1. Therapeutic response was evaluated based on the 'New Guidelines to Evaluate the Response to Treatment in Solid Tumors'.…”
Section: Editormentioning
confidence: 99%